Distribution of Major Basic Protein on Human Airway following In Vitro Eosinophil Incubation. (22nd March 2010) - Xue, Ailing; Wang, John; Sieck, Gary C.; Wylam, Mark E.
Abstract : Major basic protein (MBP) released from activated eosinophils may influence airway hyperresponsiveness (AHR) by either direct effects on airway myocytes or by an indirect effect. In this study, human bronchi, freshly isolated human eosinophils, or MBP purified from human eosinophil granules were incubated for studying eosinophil infiltration and MBP localization. Eosinophils immediately adhered to intact human airway as well as to cultured human airway myocytes and epithelium. Following incubation 18–24 h, eosinophils migrated into the airway media, including the smooth muscle layer, but had no specific recruitment to airway neurons. Eosinophils released significant amounts of MBP within the airway media, including areas comprising the smooth muscle layer. Most deposits of MBP were focally discrete and restricted by immunologic detection to a maximum volume of ∼ 300 μ m 3 about the eosinophil. Native MBP applied exogenously was immediately deposited on the surface of the airway, but required at least 1 h to become detected within the media of the airway wall. Tissue MBP infiltration and deposition increased in a time- and concentration-dependent manner. Taken together, these findings suggest that eosinophil-derived cationic proteins may alter airway hyperresponsiveness (AHR) in vivo by an effect that is not limited to the bronchial epithelium.